2022
DOI: 10.3390/diagnostics12102409
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of Neutrophil CD64 Index, PCT, and CRP in Acute Pancreatitis Complicated with Abdominal Infection

Abstract: Objective: To study the clinical diagnostic value of neutrophil CD64 index, PCT, and CRP in patients with acute pancreatitis with abdominal infection. Methods: A number of patients with acute pancreatitis (n = 234) participated in the study. According to the infection and health conditions, they were further divided into the non-infection group (n = 122), infection group (n = 78), and sepsis group (n = 34), and 40 healthy subjects were selected in the control group (n = 40). Expression levels of infection inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…We observed significantly higher CRP, neutrophils, and DNI levels in the SAP group. These findings align with the existing literature, as pancreatitis is characterized by an intense inflammatory response (19). However, it is worth noting that the median DNI value in our SAP group in our study appears to be lower than the study conducted by Kim et al in 2019, which is the only study that examines the role of DNI in pancreatitis (14).…”
Section: Discussionsupporting
confidence: 90%
“…We observed significantly higher CRP, neutrophils, and DNI levels in the SAP group. These findings align with the existing literature, as pancreatitis is characterized by an intense inflammatory response (19). However, it is worth noting that the median DNI value in our SAP group in our study appears to be lower than the study conducted by Kim et al in 2019, which is the only study that examines the role of DNI in pancreatitis (14).…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that PCT is a valuable marker in infection-related inflammatory response [20]. It has also been suggested to be a predictor of IPN, associated with morphology of necrosis and the severity of systematic complications [21]. Results of this study showed that the PCT values on the 1st, 4th, and 7th days after admission of both IPN and non-IPN group patients were above normal, with IPN patients having even higher PCT values, suggesting it as a good candidate parameter for IPN prediction.…”
Section: Discussionmentioning
confidence: 99%
“…PCT is a potential biomarker to estimate infection,which is actually valuable to guidance of antibiotic use and therapy estimation [31] .The concentration of PCT will increase in patients with AP,which is an important index to predict HTG-AP severity.The elevated procalcitonin (PCT) level was also used as a reference for the presence or absence of secondary local or systemic infection [32] .We often use CRP to estimate the degree of tissue damage and inflammation [33] ,but all predictors in this model excluded it.Considering CRP as an inflammatory response protein, it has not been fully mobilized in the early stage of the disease (within 24h) and is gradually increasing. It is also pointed out in the guidelines that serum CRP is an important indicator reflecting SIRS or infection, and serum CRP ≥ 150 mg /L indicates the severity of AP, but the evaluation time is 72 hours after the onset .…”
Section: Discussionmentioning
confidence: 99%